IMPLEMENTASI PEMBELAJARAN BERBANTUAN KOMPUTER (PBK) UNTUK MELATIH KEMANDIRIAN BELAJAR SISWA SEBAGAI WUJUD PENDIDIKAN KARAKTER - Meilani Safitri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The purpose of this study was to determine the picture of student learning independence by implementing computer-assisted learning. The subjects in this study were students of class X SMK Mandiri Palembang which consist of 20 people. The data were collected by questionnaire and interview. The results of data analysis showed that the level of student learning independence by implementing computer-assisted learning is equal to 77.35% and included in either category. PBK is an instrumental in the learning process, thus making teachers and learners accustomed to communicate to share knowledge and experience. In the learning process, learners also become more independent, capable, and creative when using the CPE. Given that independence, skill, and creativity are part of values in character education, it should be developed and used as a primary tool in learning to realize the values of character education itself.